Lithium ion secondary battery, battery module, battery pack, and electric device

By using a combination of single crystal or single crystal low-nickel ternary positive electrode material and polycrystalline high-nickel ternary positive electrode material in lithium-ion secondary batteries, the problem of limited comprehensive performance of existing lithium-ion secondary batteries is solved, and higher energy density, cycle performance and safety performance are achieved.

CN119674179AActive Publication Date: 2025-03-21CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411872828.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2021-05-20
Publication Date
2025-03-21
Estimated Expiration
2041-05-20

AI Technical Summary

Technical Problem

The existing lithium-ion secondary batteries have limited comprehensive performance in terms of high energy density, circulation performance, storage performance, gas production performance and safety performance.

Method used

The positive electrode structure is adopted that combines a bare core with single crystal or single crystal low-nickel ternary cathode material and polycrystalline high-nickel ternary cathode material, and the use ratio of single crystal and polycrystalline cathode active materials through the combination of different cathode systems.

Benefits of technology

It effectively improves the high energy density, circulation performance, storage performance, gas production performance and safety performance of lithium-ion secondary batteries, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674179A_ABST
    Figure CN119674179A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electrochemistry, in particular to a lithium ion secondary battery, a battery module, a battery pack and an electric device. The invention provides a lithium ion secondary battery which comprises a naked battery cell accommodating cavity, a naked battery cell group is arranged in the naked battery cell accommodating cavity, the naked battery cell group comprises one or more naked battery cells A and one or more naked battery cells B. The naked battery cells A comprise first positive pole pieces, the first positive pole pieces comprise first positive active materials, and the first positive active materials comprise second positive active materials. The first positive electrode active material is selected from a single-crystal or single-crystal-like low-nickel ternary positive electrode material A1, the naked battery cell B comprises a second positive electrode plate, the second positive electrode plate comprises a second positive electrode active material and / or a third positive electrode active material, the second positive electrode active material is selected from a polycrystalline high-nickel ternary positive electrode material B1, and the third positive electrode active material is selected from a polycrystalline high-nickel ternary positive electrode material B2. And the third positive electrode active material is selected from a polycrystalline low-nickel ternary positive electrode material B2. The lithium ion battery provided by the invention is relatively excellent in circulation, storage, gas production and safety performance under the conditions of high energy density and high charge state.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application based on the invention with application number: 202180006405.4, application date: May 20, 2021, applicant: Contemporary Amperex Technology Co., Ltd., and invention name: "Lithium-ion secondary battery, battery module, battery pack and electrical device". Technical Field

[0002] The present invention relates to the field of electrochemistry, and in particular to a lithium-ion secondary battery, a battery module, a battery pack and an electrical device. Background Art

[0003] Lithium-ion secondary batteries mainly rely on the back-and-forth migration of lithium ions between the positive electrode active material and the negative electrode active material to charge and discharge. Lithium-ion secondary batteries can provide stable voltage and current during use, and the use process is green and environmentally friendly, so they are widely used in various electrical devices, such as mobile phones, tablet computers, laptops, electric bicycles, electric vehicles, etc.

[0004] For high energy density, high voltage lithium-ion batteries, there is a continuous demand for improving their overall performance. In the prior art, there are structures using a variety of different positive electrode active material sub-layers, in which the positive electrode active material of one sub-layer uses a single crystal or quasi-single crystal structure of a ternary positive electrode material, and the other sub-layer uses a single crystal or quasi-single crystal structure and a polycrystalline structure of a mixed ternary positive electrode material, but similar improvements are only considered from the pole sheet level, and the improvement of the overall performance of the battery is still limited. Summary of the invention

[0005] In view of the above-mentioned shortcomings of the prior art, an object of the present invention is to provide a lithium ion secondary battery to further improve the comprehensive performance of the lithium ion secondary battery such as high energy density, cycle performance, storage performance, gas production performance and safety performance.

[0006] To achieve the above-mentioned object and other related objects, the present invention provides a lithium-ion secondary battery, including a bare cell accommodating cavity, in which a bare cell group is arranged, the bare cell accommodating cavity includes one or more bare cells A, and one or more bare cells B, the bare cell A includes a first positive electrode plate, the first positive electrode plate includes a first positive electrode active substance, the first positive electrode active substance is selected from a single crystal or quasi-single crystal low-nickel ternary positive electrode material A1, the bare cell B includes a second positive electrode plate, the second positive electrode plate includes a second positive electrode active substance and / or a third positive electrode active substance, the second positive electrode active substance is selected from a polycrystalline high-nickel ternary positive electrode material B1, and the third positive electrode active substance is selected from a polycrystalline low-nickel ternary positive electrode material B2. By using a mixed positive electrode of a bare cell including single crystal or quasi-single crystal low-nickel ternary positive electrode material and a polycrystalline high-nickel ternary positive electrode material, the characteristic of the polycrystalline high-nickel ternary positive electrode material in the delithiation state at high SOC (state of charge) can be better utilized to improve the cycle dive, thereby effectively improving the comprehensive performance of lithium-ion secondary batteries such as high energy density, cycle performance, storage performance, gas production performance and safety performance.

[0007] In any embodiment, the molecular formula of the single crystal or quasi-single crystal low-nickel ternary positive electrode material A1 is LiNi x1 Co y1 Mn 1-x1-y1 O2, wherein 0<x1≤0.65, 0<y1<0.35, 0<1-x1-y1<0.35; or the molecular formula of the single crystal or quasi-single crystal low-nickel ternary positive electrode material A1 is LiNi x1 Co y1 Mn 1-x1-y1 O2, wherein 0<x1≤0.55, 0<y1<0.45, 0<1-x1-y1<0.45. Thus, the single crystal or quasi-single crystal ternary positive electrode material with a lower nickel content ratio in the bare cell A can be combined with the polycrystalline ternary positive electrode material with a higher nickel content in the bare cell B to improve the comprehensive performance of the lithium-ion secondary battery.

[0008] In any embodiment, the molecular formula of the polycrystalline high-nickel ternary positive electrode material B1 is LiNi x2 Co y2 Mn 1-x2- y2 O2, wherein 0.7≤x2<1, 0<y2<0.3, 0<1-x2-y2<0.3; or the molecular formula of the polycrystalline high-nickel ternary positive electrode material B1 is LiNi x2 Co y2 Mn 1-x2-y2O2, where 0.7 ≤ x2 ≤ 0.8, 0.2 < y2 < 0.3, and 0.2 < 1 - x2 - y2 < 0.3. Thus, by introducing a polycrystalline ternary cathode material with a relatively high nickel content into the bare cell B, it can cooperate with the single-crystalline or quasi-single-crystalline ternary cathode material with a relatively low nickel content ratio in the bare cell A to improve the comprehensive performance of the lithium-ion secondary battery.

[0009] In any embodiment, the molecular formula of the polycrystalline low-nickel ternary cathode material B2 is LiNi x3 Co y3 Mn 1-x3- y3 O2, where 0 < x3 ≤ 0.65, 0 < y3 < 0.35, and 0 < 1 - x3 - y3 < 0.35; or the molecular formula of the polycrystalline low-nickel ternary cathode material B2 is LiNi x3 Co y3 Mn 1-x3-y3 O2, where 0 < x3 ≤ 0.55, 0 < y3 < 0.45, and 0 < 1 - x3 - y3 < 0.45. Thus, a polycrystalline ternary cathode material with a relatively low nickel content ratio can be introduced into the bare cell B. Although the introduction of this material may cause a relatively worse gas generation performance, it can generally improve the comprehensive performance of the lithium-ion secondary battery.

[0010] In any embodiment, the 100% SOC charging cell volume shrinkage rate of the single-crystalline or quasi-single-crystalline low-nickel ternary cathode material A1 ≤ 3%; and / or the 100% SOC charging cell volume shrinkage rate of the polycrystalline high-nickel ternary cathode material B1 ≥ 4%; and / or the 100% SOC charging cell volume shrinkage rate of the polycrystalline low-nickel ternary cathode material B2 ≤ 3%. Thus, by selecting the 100% SOC charging cell volume shrinkage rate, the property of lattice shrinkage of the ternary cathode material at high SOC can be better reflected.

[0011] In any embodiment, compared with the bare cell A, the bare cell B is distributed closer to the outside of the bare cell group. Thus, placing the bare cell B on the outermost side of the bare cell group is similar to providing a buffer layer to buffer the bare cell A, thereby effectively avoiding the swelling problem caused by the obvious growth trend of the swelling force of the bare cell during the charging process.

[0012] In any embodiment, compared with the bare cell B, the bare cell A is distributed closer to the middle of the bare cell group. This is because the bare cell in the middle area of the cell usually has a more obvious temperature rise and is more conducive to the infiltration of the electrolyte. Distributing the bare cell A in the middle of the bare cell group can further avoid the situation of large-area lithium deposition in the bare cell A due to large swelling force and insufficient infiltration of the electrolyte in the middle area.

[0013] In any embodiment, the second positive electrode sheet further includes a fourth positive electrode active material, and the fourth positive electrode active material is selected from single crystal or quasi-single crystal low-nickel ternary positive electrode material A2, and the molecular formula of the single crystal or quasi-single crystal low-nickel ternary positive electrode material A2 is LiNi x4 Co y4 Mn 1-x4-y4 O2, where 0 < x4 ≤ 0.65, 0 < y4 < 0.35, 0 < 1 - x4 - y4 < 0.35; alternatively, the second positive electrode sheet further includes a fourth positive electrode active material, and the fourth positive electrode active material is selected from single crystal or quasi-single crystal low-nickel ternary positive electrode material A2, and the molecular formula of the single crystal or quasi-single crystal low-nickel ternary positive electrode material A2 is LiNi x4 Co y4 Mn 1-x4-y4 O2, where 0 < x4 ≤ 0.55, 0 < y4 < 0.45, 0 < 1 - x4 - y4 < 0.45. Thus, the single crystal or quasi-single crystal ternary positive electrode material with a relatively low nickel content ratio within the above numerical range has good gas generation performance, and when combined with the ternary positive electrode material with a relatively high nickel content in the bare battery cell B, it can improve the comprehensive performance of the lithium-ion secondary battery.

[0014] In any embodiment, the 100% SOC charging cell volume shrinkage rate of the single crystal or quasi-single crystal low-nickel ternary positive electrode material A2 ≤ 3%. By selecting the 100% SOC charging cell volume shrinkage rate, the property of lattice shrinkage of the ternary positive electrode material at high SOC can be better reflected.

[0015] In any embodiment, in the lithium-ion secondary battery, the mass ratio k of the total mass of the single crystal positive electrode active material to the total mass of the polycrystalline positive electrode active material is 0.5 to 9. Thus, the lithium-ion secondary battery as a whole can have better comprehensive performance.

[0016] In any embodiment, the coating amount of the negative electrode in the bare battery cell A ≤ 0.150 g / 1540.25 mm^2. Thus, when the coating amount of the negative electrode of the bare battery cell A is within the above range, it is more conducive to improving the negative electrode kinetics and avoiding large-scale lithium deposition due to excessive expansion growth and insufficient electrolyte infiltration in the bare battery cell A with obvious expansion growth.

[0017] The second aspect of the present application provides a battery module, including the lithium-ion secondary battery of the first aspect of the present application.

[0018] The third aspect of the present application provides a battery pack, including the battery module of the second aspect of the present application.

[0019] The fourth aspect of the present application provides an electrical device, including one or more of the lithium-ion secondary battery of the second aspect of the present application, the battery module of the third aspect of the present application, or the battery pack of the fifth aspect of the present application.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The lithium-ion battery provided by the present invention includes single crystal or quasi-single crystal low-nickel ternary positive electrode materials and polycrystalline high-nickel ternary positive electrode materials, each of which is located in different bare cells. By matching bare cells of different positive electrode systems, the ratio of single crystal low-nickel positive electrode active materials to polycrystalline high-nickel positive electrode active materials in the entire battery can be better optimized, thereby obtaining a lithium-ion secondary battery with excellent circulation, storage, gas production and safety performance under high energy density and high charge state. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Shown is a schematic diagram of the position of the bare cell in the bare cell accommodating cavity in Example 1 of the present invention.

[0023] Figure 2 It is a schematic diagram of a lithium ion secondary battery according to one embodiment of the present application.

[0024] Figure 3 yes Figure 2 An exploded view of a lithium-ion secondary battery according to an embodiment of the present application is shown.

[0025] Figure 4 is a schematic diagram of a battery module according to an embodiment of the present application.

[0026] Figure 5 It is a schematic diagram of a battery pack according to one embodiment of the present application.

[0027] Figure 6 yes Figure 5 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0028] Figure 7 Schematic diagram of a device using a lithium ion secondary battery according to an embodiment of the present application as a power source.

[0029] Figure 8 A schematic diagram showing the change in unit cell volume of a positive electrode of a positive electrode active material used in one embodiment of the present application at different delithiation states (SOC).

[0030] Fig. 9 Shown is a schematic diagram of the design of a synchrotron radiation in-situ XRD electrolytic cell used in one embodiment of the present application.

[0031] Component number description

[0032] 1 Battery Pack

[0033] 2 upper box

[0034] 3 lower box

[0035] 4 Battery Module

[0036] 5 Lithium-ion secondary battery

[0037] 51 Shell

[0038] 52 Electrode assembly

[0039] 53 Top cover assembly DETAILED DESCRIPTION

[0040] In order to make the invention objectives, technical solutions and beneficial technical effects of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. People familiar with this technology can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0041] For simplicity, the application only clearly discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form a scope that is not clearly recorded, and any lower limit can be combined with other lower limits to form a scope that is not clearly recorded, and any upper limit can be combined with any other upper limit to form a scope that is not clearly recorded. In addition, although it is not clearly recorded, each point or single value between the range endpoints is included in the scope. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or form a scope that is not clearly recorded with other lower limits or upper limits.

[0042] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” are inclusive of the number, and “multiple” in “one or more” means more than two.

[0043] The above summary of the invention of the present invention is not intended to describe each disclosed embodiment or each implementation in the present invention. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of embodiments, which can be used in various combinations. In each embodiment, enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0044] Lithium-ion secondary battery

[0045] In one embodiment of the present application, the present invention provides a lithium-ion secondary battery, including a bare cell accommodating cavity, a bare cell group is provided in the bare cell accommodating cavity, the bare cell group includes one or more bare cells A, and one or more bare cells B, the bare cell A includes a first positive electrode plate, the first positive electrode plate includes a first positive electrode active substance, the first positive electrode active substance is selected from a single crystal or quasi-single crystal low-nickel ternary positive electrode material A1, the bare cell B includes a second positive electrode plate, the second positive electrode plate includes a second positive electrode active substance and / or a third positive electrode active substance, the second positive electrode active substance is selected from a polycrystalline high-nickel ternary positive electrode material B1, and the third positive electrode active substance is selected from a polycrystalline low-nickel ternary positive electrode material B2. Compared with single crystal or quasi-single crystal low-nickel ternary positive electrode materials, polycrystalline high-nickel ternary positive electrode materials have a more obvious lattice contraction effect at high SOC (for example, ≥65% SOC, ≥64% SOC, ≥63% SOC, ≥62% SOC, ≥61% SOC, ≥60% SOC, ≥59% SOC, ≥58% SOC, ≥57% SOC, ≥56% SOC, or ≥55% SOC), which can effectively alleviate the influence of force on the negative electrode during charging and reduce the risk of lithium deposition due to large expansion force of the negative electrode and cycle diving due to lithium deposition. However, at high SOC, polycrystalline high-nickel ternary positive electrode materials are at risk of worsening gas production and reduced safety performance, and their storage is also significantly worse than that of single crystal low-nickel materials. The inventors of the present application unexpectedly discovered that by using a mixed positive electrode of a bare cell comprising a single crystal or quasi-single crystal low-nickel ternary positive electrode material and a polycrystalline high-nickel ternary positive electrode material, compared to physically mixing single crystal and polycrystalline in a single bare cell or using a double-layer design of single crystal or polycrystalline, the polycrystalline high-nickel ternary positive electrode material can better utilize the more obvious lattice shrinkage of the polycrystalline high-nickel ternary positive electrode material in the delithiation state at high SOC to improve cycle diving, thereby effectively improving the comprehensive performance of lithium-ion secondary batteries (for example, cycle life, etc.).

[0046] In the present application, the single crystal structure of the ternary positive electrode material generally refers to the primary particles without obvious agglomeration (the volume distribution of the secondary particles formed by a very small amount of agglomeration accounts for less than 5%). The primary particle volume average particle size (D V50 ) can be generally 1-10 μm, 1-2 μm, 2-3 μm, 3-4 μm, 4-5 μm, 5-6 μm, 6-7 μm, 7-8 μm, 8-9 μm, or 9-10 μm. For example, the single crystal structure of the ternary positive electrode material can be LiNi 0.55 Co 0.15 Mn 0.30 O2, LiNi 0.55 Co 0.05 Mn 0.40 O2, LiNi 0.65 Co 0.07 Mn 0.28O2, etc. The ternary cathode material with a quasi-single-crystal structure usually refers to a ternary cathode material with slightly agglomerated primary particles (the volume distribution of secondary particles formed by agglomeration accounts for 10% to 35%). For example, the ternary cathode material with a quasi-single-crystal structure can be LiNi 0.56 Co 0.12 Mn 0.32 O2, etc. The polycrystalline structure ternary positive electrode material refers to the secondary spherical particles formed by the agglomeration of primary particles. For example, the polycrystalline structure ternary positive electrode material with a relatively high nickel content can be LiNi 0.70 Co 0.10 Mn 0.20 O2、LiNi 0.80 Co 0.10 Mn 0.10 O2, etc. For another example, the polycrystalline ternary positive electrode material with relatively low nickel content can be LiNi 0.56 Co 0.12 Mn 0.32 O2, etc.

[0047] In some embodiments, the positive electrode active material included in the bare battery cell A may mainly include a first positive electrode active material, which may generally be a single crystal or quasi-single crystal low-nickel ternary positive electrode material A1, whose molecular formula may be LiNi x1 Co y1 Mn 1-x1-y1O2. Among them, x1 can usually satisfy 0<x1≤0.65, 0<x1≤0.05, 0.05≤x1≤0.1, 0.1≤x1≤0.15, 0.15≤x1≤0.2, 0.2≤x1≤0.25, 0.25≤x1≤0.3, 0.3≤x1≤0.35, 0.35≤x1≤0.4, 0.4≤x1≤0.45, 0.45≤x1≤0.5, 0.5≤x1≤0.0.55, 0.55≤x1≤0.6, or 0.6≤x1≤0.65, and preferably can satisfy 0<x1≤0.55. y1 can usually satisfy 0<y1<0.45, 0<y1≤0.05, 0.05≤y1≤0.1, 0.1≤y1≤0.15, 0.15≤y1≤0.2, 0.2≤y1≤0.25, 0.25≤y1≤0.3, 0.3≤y1<0.35, 0.35≤y1<0.4, or 0.4≤y1<0.45. Generally speaking, the preferred value range of y1 corresponds to the preferred value range of x1. When x1 can satisfy 0<x1≤0.55, y1 can usually satisfy 0<y1<0.45. 1-x1-y1 can usually satisfy 0<1-x1-y1<0.45, 0<1-x1- y1≤0.05, 0.05≤1-x1-y1≤0.1, 0.1≤1-x1-y1≤0.15, 0.15≤1-x1-y1≤0.2, 0.2≤1-x1-y1≤0.25, 0.25≤1-x1-y1≤0.3, 0.3≤1-x1-y1<0.35, 0.35≤1-x1-y1<0.4, or 0.4≤1-x1-y1<0.45. Generally speaking, the preferred value range of 1-x1-y1 corresponds to the preferred value range of x1. When x1 can satisfy 0<x1≤0.55, 1-x1-y1 can generally satisfy 0<1-x1-y1<0.45. The lattice contraction property of the ternary positive electrode material at high SOC can be reflected by the nickel content in the material. Generally speaking, the lattice contraction effect of single crystal or quasi-single crystal ternary positive electrode materials with a lower nickel content ratio is relatively unobvious, but the gas production performance will be better. The single crystal or quasi-single crystal ternary positive electrode materials with a lower nickel content ratio in bare cell A can be combined with the polycrystalline ternary positive electrode materials with a higher nickel content in bare cell B to improve the comprehensive performance of lithium-ion secondary batteries.

[0048] In some embodiments, the 100% SOC charging unit cell volume shrinkage rate of the single crystal or quasi-single crystal low-nickel ternary positive electrode material A1 is generally ≤3%, and the specific measurement method of the 100% SOC charging unit cell volume shrinkage rate can refer to the measurement method given in the embodiment of the present invention. By selecting the 100% SOC charging unit cell volume shrinkage rate, the lattice shrinkage property of the ternary positive electrode material at high SOC can be more accurately reflected.

[0049] In some embodiments, the positive electrode active material included in the bare battery cell B may include a second positive electrode active material, which may generally be a polycrystalline high-nickel ternary positive electrode material B1, whose molecular formula may be LiNix2Co y2 Mn 1-x2-y2 O2. Among them, x2 can usually satisfy 0.7≤x2<1, 0.7≤x2≤0.75, 0.75≤x2≤0.8, 0.8≤x2≤0.85, 0.85≤x2≤0.9, 0.9≤x2≤0.95, 0.95≤x2<1, and preferably can satisfy 0.7≤x2≤0.8. y2 can usually satisfy 0<y2<0.3, 0<y2≤0.05, 0.05≤y2≤0.1, 0.1≤y2≤0.15, 0.15≤y2≤0.2, 0.2≤y2≤0.25, or 0.25≤y2<0.3. Generally speaking, the preferred value range of y2 corresponds to the preferred value range of x2. When x2 can satisfy 0.7≤x2≤0.8, y2 can usually satisfy 0.2<y2<0.3. 1-x2-y2 can usually satisfy 0<1-x2-y2<0.3, 0<1-x2-y2≤0.05, 0.05≤1-x2-y2≤0.1, 0.1≤1-x2-y2≤0.15, 0.15≤1-x2-y2≤0.2, 0.2≤1-x2-y2≤0.25, or 0.25≤1-x2-y2<0.3. Generally speaking, the preferred value range of 1-x2-y2 corresponds to the preferred value range of x2. When x2 can satisfy 0.7≤x2≤0.8, 1-x2-y2 can usually satisfy 0.2<1-x2-y2<0.3. The lattice contraction property of the ternary positive electrode material at high SOC can be reflected by the nickel content in the material. Generally speaking, the lattice contraction effect of the polycrystalline ternary positive electrode material with a higher nickel content ratio is relatively more obvious, but the gas production performance will be poor. The introduction of polycrystalline ternary positive electrode material with a higher nickel content in the bare battery cell B can be combined with the single crystal or quasi-single crystal ternary positive electrode material with a lower nickel content ratio in the bare battery cell A to improve the comprehensive performance of the lithium-ion secondary battery.

[0050] In some embodiments, the 100% SOC charging unit cell volume shrinkage rate of the polycrystalline high-nickel ternary positive electrode material B1 is generally ≥4%. By selecting the 100% SOC charging unit cell volume shrinkage rate, the lattice shrinkage property of the ternary positive electrode material at high SOC can be more accurately reflected.

[0051] In some embodiments, the positive electrode active material included in the bare battery cell B may include a third positive electrode active material, which may generally be a polycrystalline low-nickel ternary positive electrode material B2, whose molecular formula may be LiNi x3 Co y3 Mn 1-x3-y3O2. Among them, x3 generally satisfies 0 < x3 ≤ 0.65, 0 < x3 ≤ 0.05, 0.05 ≤ x3 ≤ 0.1, 0.1 ≤ x3 ≤ 0.15, 0.15 ≤ x3 ≤ 0.2, 0.2 ≤ x3 ≤ 0.25, 0.25 ≤ x3 ≤ 0.3, 0.3 ≤ x3 ≤ 0.35, 0.35 ≤ x3 ≤ 0.4, 0.4 ≤ x3 ≤ 0.45, 0.45 ≤ x3 ≤ 0.5, 0.5 ≤ x3 ≤ 0.55, 0.55 ≤ x3 ≤ 0.6, or 0.6 ≤ x3 ≤ 0.65, preferably satisfies 0 < x3 ≤ 0.55. y3 generally satisfies 0 < y3 < 0.45, 0 < y3 ≤ 0.05, 0.05 ≤ y3 ≤ 0.1, 0.1 ≤ y3 ≤ 0.15, 0.15 ≤ y3 ≤ 0.2, 0.2 ≤ y3 ≤ 0.25, 0.25 ≤ y3 ≤ 0.3, 0.3 ≤ y3 < 0.35, 0.35 ≤ y3 < 0.4, or 0.4 ≤ y3 < 0.45. Generally speaking, the preferred value range of y3 corresponds to the preferred value range of x3. When x3 satisfies 0 < x3 ≤ 0.55, y3 generally satisfies 0 < y3 < 0.45. 1 - x3 - y3 generally satisfies 0 < 1 - x3 - y3 < 0.45, 0 < 1 - x3 - y3 ≤ 0.05, 0.05 ≤ 1 - x3 - y3 ≤ 0.1, 0.1 ≤ 1 - x3 - y3 ≤ 0.15, 0.15 ≤ 1 - x3 - y3 ≤ 0.2, 0.2 ≤ 1 - x3 - y3 ≤ 0.25, 0.25 ≤ 1 - x3 - y3 ≤ 0.3, 0.3 ≤ 1 - x3 - y3 < 0.35, 0.35 ≤ 1 - x3 - y3 < 0.4, or 0.4 ≤ 1 - x3 - y3 < 0.45. Generally speaking, the preferred value range of 1 - x3 - y3 corresponds to the preferred value range of x3. When x3 satisfies 0 < x3 ≤ 0.55, 1 - x3 - y3 generally satisfies 0 < 1 - x3 - y3 < 0.45. In the bare cell B, a polycrystalline ternary cathode material with a relatively low nickel content ratio can be introduced. The secondary particles of the polycrystalline ternary cathode material with a relatively low nickel content ratio are relatively easy to break, which can improve the swelling growth during the cycling process. Although the introduction of this material may cause the gas generation performance to deteriorate relatively, overall, it can improve the comprehensive performance of the lithium-ion secondary battery.

[0052] In some embodiments, in the lithium-ion secondary battery, the 100% SOC charging cell volume shrinkage rate of the polycrystalline low-nickel ternary cathode material B2 is generally ≤ 3%. By selecting the 100% SOC charging cell volume shrinkage rate, the property of the ternary cathode material's lattice shrinkage at high SOC can be more accurately reflected.

[0053] In some embodiments, compared to bare cell A, bare cell B may be distributed closer to the outside of the bare cell group, while compared to bare cell B, bare cell A may be distributed closer to the middle of the bare cell group. This distribution trend may be the overall distribution trend of one or more bare cells A compared to one or more bare cells B, or it may be the individual positional relationship between a single bare cell A and a single bare cell B. Since the polycrystalline high-nickel ternary positive electrode material B1 included in the bare cell B has a more obvious lattice contraction at high SOC, the expansion force of the bare cell increases slowly during charging, while the single crystal or quasi-single crystal low-nickel ternary positive electrode material A1 included in the bare cell A has an insignificant lattice contraction at high SOC, and the bare cell expansion force increases significantly during charging, so the bare cell B is placed further outside the bare cell group, similar to providing a buffer layer to buffer the bare cell A. In addition, since the temperature rise of the bare cell in the middle area of ​​the battery cell is usually more obvious and more conducive to electrolyte infiltration, distributing the bare cell A in the middle of the bare cell group can further avoid large-area lithium deposition of the bare cell A due to large expansion force and insufficient electrolyte infiltration in the middle area.

[0054] In some embodiments, the second positive electrode plate further includes a fourth positive electrode active material, the fourth positive electrode active material is selected from a single crystal or quasi-single crystal low-nickel ternary positive electrode material A2, the molecular formula of the single crystal or quasi-single crystal low-nickel ternary positive electrode material A2 can be LiNi x4 Co y4 Mn 1-x4-y4O2. Among them, x4 can generally satisfy 0 < x4 ≤ 0.65, 0 < x4 ≤ 0.05, 0.05 ≤ x4 ≤ 0.1, 0.1 ≤ x4 ≤ 0.15, 0.15 ≤ x4 ≤ 0.2, 0.2 ≤ x4 ≤ 0.25, 0.25 ≤ x4 ≤ 0.3, 0.3 ≤ x4 ≤ 0.35, 0.35 ≤ x4 ≤ 0.4, 0.4 ≤ x4 ≤ 0.45, 0.45 ≤ x4 ≤ 0.5, 0.5 ≤ x4 ≤ 0.55, 0.55 ≤ x4 ≤ 0.6, or 0.6 ≤ x4 ≤ 0.65. y4 can generally satisfy 0 < y4 < 0.45, 0 < y4 ≤ 0.05, 0.05 ≤ y4 ≤ 0.1, 0.1 ≤ y4 ≤ 0.15, 0.15 ≤ y4 ≤ 0.2, 0.2 ≤ y4 ≤ 0.25, 0.25 ≤ y4 ≤ 0.3, 0.3 ≤ y4 < 0.35, 0.35 ≤ y4 < 0.4, or 0.4 ≤ y4 < 0.45. Generally speaking, the preferred value range of y4 corresponds to the preferred value range of x4. When x4 can satisfy 0 < x4 ≤ 0.55, y4 can generally satisfy 0 < y4 < 0.45. 1 - x4 - y4 can generally satisfy 0 < 1 - x4 - y4 < 0.45, 0 < 1 - x4 - y4 ≤ 0.05, 0.05 ≤ 1 - x4 - y4 ≤ 0.1, 0.1 ≤ 1 - x4 - y4 ≤ 0.15, 0.15 ≤ 1 - x4 - y4 ≤ 0.2, 0.2 ≤ 1 - x4 - y4 ≤ 0.25, 0.25 ≤ 1 - x4 - y4 ≤ 0.3, 0.3 ≤ 1 - x4 - y4 < 0.35, 0.35 ≤ 1 - x4 - y4 < 0.4, or 0.4 ≤ 1 - x4 - y4 < 0.45. Generally speaking, the preferred value range of 1 - x4 - y4 corresponds to the preferred value range of x4. When x4 can satisfy 0 < x4 ≤ 0.55, 1 - x4 - y4 can generally satisfy 0 < 1 - x4 - y4 < 0.45. In the bare cell B, a single crystal or pseudo-single crystal ternary cathode material with a relatively low nickel content ratio can be further introduced. As described above, the lattice contraction effect of the single crystal or pseudo-single crystal ternary cathode material with a relatively low nickel content ratio is relatively not obvious, but the gas generation performance is better. When combined with the ternary cathode material with a relatively high nickel content in the bare cell B, the overall comprehensive performance of the lithium-ion secondary battery can be improved. The usage amount of the single crystal or pseudo-single crystal low-nickel ternary cathode material A2 in the bare cell B can be adjusted and optimized based on the actual performance requirements of the cell. When the gas generation demand for the bare cell is high, the proportion of the single crystal or pseudo-single crystal low-nickel ternary cathode material A2 in the bare cell B can be appropriately increased, and the proportion of the polycrystalline high-nickel ternary cathode material B1 can be reduced.

[0055] In some embodiments, the 100% SOC charging cell volume shrinkage rate of the single crystal or pseudo-single crystal low-nickel ternary cathode material A2 is generally ≤ 3%. By selecting the 100% SOC charging cell volume shrinkage rate, the property of lattice contraction of the ternary cathode material at high SOC can be more accurately reflected.

[0056] In some embodiments, in the entire battery system, the mass ratio k of the total mass of single crystal positive electrode active material (for example, including single crystal or quasi-single crystal low nickel ternary positive electrode material A1, single crystal or quasi-single crystal low nickel ternary positive electrode material A2, etc.) and the total mass of polycrystalline positive electrode active material (for example, including polycrystalline high nickel ternary positive electrode material B1, polycrystalline low nickel ternary positive electrode material B2, etc.) can be 0.5-9, 0.5-1, 1-1.5, 1.5-2, 2-2.5, 2.5-3, 3-3.5, 3.5-4, 4-4.5, 4.5-5, 5-5.5, 5.5-6, 6-6.5, 6.5-7, 7-7.5, 7.5-8, 8-8.5, or 8.5-9. The mass ratio k can usually be adjusted by the ratio of bare cell A and bare cell B, or the ratio of each ternary positive electrode material included in bare cell A or bare cell B. Generally speaking, when the mass ratio k satisfies the above range, the lithium-ion secondary battery can have better overall performance as a whole. The reason may be that when the proportion of polycrystalline positive electrode active material is too large, the gas production performance of the lithium-ion battery may deteriorate, and when the proportion of polycrystalline positive electrode active material is too small, the improvement of cycle expansion may not be sufficient. Therefore, in the later stage of the battery cycle, due to the large expansion force, lithium is easily deposited in the middle of the bare cell, and the cycle is reduced.

[0057] In some embodiments, the coating amount of the positive electrode in bare cell A and bare cell B may be substantially the same or different, and the coating amount of the negative electrode in bare cell A and bare cell B may also be substantially the same or different. However, the coating amount of the negative electrode of bare cell A is generally not too large. For example, the coating amount of the negative electrode in bare cell A may be ≤0.150g / 1540.25mm^2. The coating amount of the negative electrode of bare cell A may be relatively small, which may be more conducive to improving the negative electrode dynamics and avoiding the large-area lithium deposition of bare cell A with obvious expansion growth due to excessive expansion growth and insufficient electrolyte infiltration. Correspondingly, bare cell B relieves the stress on the negative electrode due to the lattice contraction of the polycrystalline positive electrode material, and will not cause large-area lithium deposition due to the large expansion force. Therefore, the coating amount of the negative electrode in bare cell B may be relatively large. The two can be adjusted in coordination to meet the capacity and energy density requirements of the entire cell.

[0058] In some embodiments, each ternary positive electrode material (for example, single crystal or quasi-single crystal low-nickel ternary positive electrode material A1, single crystal or quasi-single crystal low-nickel ternary positive electrode material A2, polycrystalline high-nickel ternary positive electrode material B1, polycrystalline low-nickel ternary positive electrode material B2, etc.) can be independently a ternary positive electrode material after coating modification. Generally speaking, after appropriate coating modification, the comprehensive performance of the ternary positive electrode material (for example, gas production and other performance) can usually be improved, but on the whole, the lattice contraction property of the ternary positive electrode material at high SOC is still closely related to the nickel content in the ternary positive electrode material and / or the 100% SOC charging unit cell volume shrinkage rate. Suitable methods for coating and modifying ternary positive electrode materials should be known to those skilled in the art. For example, the gas production performance of the ternary material can be improved by coating lithium iron phosphate nanoparticles on the surface of the high-nickel ternary material.

[0059] Typically, the lithium-ion secondary battery provided in the present application may include a bare cell A and / or a bare cell B, and the bare cell A and / or the bare cell B may include a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator, etc. During the battery charge and discharge process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0060] In the lithium-ion secondary battery provided in the present application, the bare cell A and the bare cell B can each independently include the first positive electrode sheet, the second positive electrode sheet, etc. as described above. The positive electrode sheet can generally include a positive electrode collector and a positive electrode film layer arranged on at least one surface of the positive electrode collector. The composition of the positive electrode active material in the positive electrode film layer can be as described above.

[0061] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.

[0062] In the lithium-ion secondary battery provided in the present application, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0063] The positive electrode film layer may also optionally include a conductive agent. However, there is no specific limitation on the type of the conductive agent, and those skilled in the art may select it according to actual needs. As an example, the conductive agent used for the positive electrode film layer may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.

[0064] In the present application, the positive electrode sheet can be prepared according to methods known in the art. As an example, the positive electrode active material, conductive agent and binder of the present application can be dispersed in a solvent (such as N-methylpyrrolidone (NMP)) to form a uniform positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet is obtained.

[0065] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer arranged on at least one surface of the negative electrode current collector, and the negative electrode film layer includes a negative electrode active material.

[0066] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0067] In the lithium-ion secondary battery provided in the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0068] In the lithium-ion secondary battery provided in the present application, the negative electrode film layer generally comprises a negative electrode active material and an optional binder, an optional conductive agent and other optional additives, and is generally formed by coating and drying a negative electrode slurry. The negative electrode slurry coating is generally formed by dispersing the negative electrode active material and the optional conductive agent and binder in a solvent and stirring them uniformly. The solvent may be N-methylpyrrolidone (NMP) or deionized water.

[0069] As an example, the conductive agent may be selected from one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0070] As an example, the binder can be selected from one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).

[0071] Other optional auxiliary agents include, for example, thickeners (such as sodium carboxymethyl cellulose (CMC-Na)).

[0072] In the lithium-ion secondary battery provided in the present application, the negative electrode film layer may optionally include other commonly used negative electrode active materials in addition to the negative electrode active material. For example, as other commonly used negative electrode active materials, artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate can be listed. The silicon-based material may be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites and silicon alloys. The tin-based material may be selected from one or more of elemental tin, tin oxide compounds and tin alloys.

[0073] The electrolyte plays the role of conducting ions between the positive electrode plate and the negative electrode plate. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolyte).

[0074] In some embodiments, the electrolyte may be an electrolyte solution, which may include an electrolyte salt and a solvent.

[0075] In some embodiments, the electrolyte salt can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).

[0076] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0077] In some embodiments, the electrolyte may also optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.

[0078] Lithium-ion secondary batteries using electrolytes and some lithium-ion secondary batteries using solid electrolytes also include a separator. The separator is arranged between the positive electrode plate and the negative electrode plate to play an isolating role. The present application has no particular restrictions on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected. In some embodiments, the material of the separator can be selected from one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film, without particular restrictions. When the separator is a multi-layer composite film, the materials of each layer can be the same or different, without particular restrictions.

[0079] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.

[0080] In some embodiments, the lithium-ion secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0081] In some embodiments, the outer packaging of the lithium ion secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the lithium ion secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and as plastic, polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS) can be listed.

[0082] The present application has no particular limitation on the shape of the lithium-ion secondary battery, which may be cylindrical, square, or any other shape. Figure 2 The lithium ion secondary battery 5 is a square structure as an example.

[0083] In some embodiments, reference Figure 3 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the lithium-ion secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0084] Battery Module

[0085] In some embodiments, lithium-ion secondary batteries can be assembled into a battery module. The number of lithium-ion secondary batteries contained in the battery module can be one or more, and the specific number can be selected by those skilled in the art according to the application and capacity of the battery module.

[0086] Figure 4 4 is an example of a battery module. Figure 4 In the battery module 4, the plurality of lithium-ion secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of lithium-ion secondary batteries 5 may be fixed by fasteners.

[0087] Optionally, the battery module 4 may further include a housing having a housing space, and the plurality of lithium-ion secondary batteries 5 are housed in the housing space.

[0088] Battery Pack

[0089] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0090] Figure 5 and Figure 6 1 is a battery pack 1 as an example. Figure 5 and Figure 6 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0091] Electrical devices

[0092] In addition, the present application also provides an electrical device, which may include one or more of the lithium-ion secondary batteries, battery modules, or battery packs provided in the present application. The above-mentioned lithium-ion secondary batteries, battery modules, or battery packs can be used as the power source of the device, and can also be used as the energy storage unit of the device. The above-mentioned electrical device can be, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0093] As the above-mentioned electrical device, a lithium-ion secondary battery, a battery module or a battery pack can be selected according to its use requirements.

[0094] Figure 7 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of lithium-ion secondary batteries, a battery pack or a battery module can be used.

[0095] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a lithium-ion secondary battery may be used as a power source.

[0096] The present application is further described below by way of examples, but the scope of the present application is not limited thereby.

[0097] The main materials and parameter information used in the examples are as follows:

[0098] Single crystal NCM523(LiNi 0.55 Co 0.15 Mn 0.3 O2), 4.35V full battery first cycle discharge capacity ~182mAh / g, 100% SOC unit cell volume shrinkage ~2.27%;

[0099] Polycrystalline NCM712(LiNi 0.7 Co 0.10 Mn 0.2 O2), 4.35V full battery first cycle discharge capacity ~197mAh / g, 100% SOC unit cell volume shrinkage ~4.04%;

[0100] Polycrystalline NCM523(LiNi 0.56 Co 0.12 Mn 0.32O2), 4.35V full battery first cycle discharge capacity ~182mAh / g, 100% SOC unit cell volume shrinkage ~2.30%.

[0101] The active mass ratio k in the entire battery cell = the mass of the single crystal positive electrode active material / the mass of the polycrystalline positive electrode active material, wherein the single crystal positive electrode active material includes the above-mentioned single crystal NCM523, etc., and the polycrystalline positive electrode active material includes the above-mentioned polycrystalline NCM712, polycrystalline NCM523, etc.

[0102] Example 1

[0103] Preparation of positive electrode sheet: Using single crystal NCM523 of ternary positive electrode material as positive electrode active material, carbon black as conductive agent, and polyvinylidene fluoride as adhesive, the mass ratio of the three is 96:2:2. Using N-methylpyrrolidone as solvent, the solid content of the slurry is 64%, and after mixing evenly, the positive electrode slurry is formed, and the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil (double-sided coating); drying, and then cold pressing, trimming, cutting, and striping to form a positive electrode sheet, the single-sided coating amount of the foil is 0.260g / 1540.25mm 2 (Total mass of mixed materials, excluding base material).

[0104] Preparation of negative electrode sheet: artificial graphite is used as negative electrode active material, carbon black is used as conductive agent, styrene-butadiene rubber (SBR) (solid content 0.48) is used as adhesive, and thickener sodium carboxymethyl cellulose is added. The mixture is stirred and mixed evenly in a mass ratio of 96.9:0.5:1.5:1.1 to form negative electrode slurry, and the negative electrode slurry is evenly coated on the negative electrode current collector copper foil (double-sided coating); drying, and then cold pressing, trimming, cutting, and striping are performed to form negative electrode sheets. The single-sided coating amount of the foil is 0.155g / 1540.25mm 2 (Total mass of mixed materials, excluding base material).

[0105] Preparation of isolation membrane: Take a polyethylene film with a thickness of 7μm as the isolation membrane substrate; then use the micro-concave coating method to control the amount of slurry to apply the inorganic oxide layer slurry to one side of the 7μm thick isolation membrane substrate (polyethylene). The inorganic oxide layer slurry consists of inorganic aluminum oxide powder, polyvinyl pyrrolidone, and solvent acetone, with a mixing mass ratio of 3:1:6. After oven drying, an isolation membrane with a first coating is obtained. Polyvinylidene fluoride (PVDF), acetone solvent, and ethyl acetate are stirred and mixed in a mass ratio of 5:40:55 to form a slurry, and then the above slurry is sprayed on the isolation membrane with the first coating. The single-side thickness of the second coating is 1μm. After oven drying, the second coating is formed on the first coating to obtain the final isolation membrane.

[0106] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell A.

[0107] The preparation process of bare cell B is the same as that of bare cell A, except that the positive electrode active material uses ternary positive electrode material polycrystalline NCM712, and the weight of the positive electrode sheet coated on one side is 0.257g / 1540.25mm 2 (excluding substrate), the weight of the positive electrode coating on one side is 0.163g / 1540.25mm 2 (without substrate), and the pole piece lengths are slightly different.

[0108] The battery cell assembly process is as follows Figure 1 As shown in the figure, A represents bare cell A, B represents bare cell B, and the volume of the inner cavity is 47582mm 3 In the bare cell accommodating chamber (rectangular space), bare cell B is placed in the outer areas ① and ④, and bare cell A is placed in the middle areas ② and ③. The electrolyte composition is: 1 mol / L lithium hexafluorophosphate (LiPF6), the solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC), and the volume ratio of solvent EC:DMC is 9:1. The battery is made after the processes of liquid injection, formation, exhaust, and sealing.

[0109] The active mass ratio k in the entire battery cell is 1.08.

[0110] Example 2

[0111] The preparation process of the lithium-ion battery is generally similar to that of Example 1, except that there is only one bare cell B, which is distributed in region ④, and the active mass ratio k in the entire cell is 3.44.

[0112] Example 3

[0113] The preparation process of the lithium-ion battery is generally referred to Example 1, except that the positive electrode active material of the bare battery cell B is a physical mixture of single crystal NCM523 + polycrystalline NCM712, the mixing mass ratio is 5:5, and the active mass ratio k in the whole battery cell is 3.13.

[0114] Example 4

[0115] The preparation process of the lithium-ion battery is generally referred to Example 1, except that the positive electrode active material of the bare battery cell B is a physical mixture of single crystal NCM523 + polycrystalline NCM712, the mixing mass ratio is 7:3, and the active mass ratio k in the whole battery cell is 5.85.

[0116] Example 5

[0117] The preparation process of the lithium-ion battery is generally similar to that of Example 1, except that the positive electrode active material of the bare cell B is polycrystalline Ni55, and the active mass ratio k in the entire cell is 1.00.

[0118] Example 6

[0119] The preparation process of the lithium-ion battery is generally similar to that of Example 1, except that the number of layers of the bare cell A is different, and the active mass ratio k in the entire cell is 1.07.

[0120] Example 7

[0121] The preparation process of the lithium-ion battery is generally similar to that of Example 3, except that the single crystal NCM523 is replaced by polycrystalline NCM523 in the bare cell B, and the active mass ratio k in the entire cell is 1.06.

[0122] Example 8

[0123] The preparation process of the lithium-ion battery is generally referred to Example 1, except that the bare cell A is placed in the outer areas ① and ④, the bare cell B is placed in the middle areas ② and ③, and the active mass ratio k in the entire cell is 1.08.

[0124] Example 9

[0125] The preparation process of the lithium-ion battery is generally referred to Example 1, except that the positive electrode active material of the bare battery cell B is a physical mixture of single crystal NCM523 + polycrystalline NCM712, the mixing mass ratio is 8:2, and the active mass ratio k in the entire battery cell is 9.26.

[0126] Example 10

[0127] The preparation process of the lithium-ion battery is generally referred to Example 1, except that the bare cell A is placed in the middle area ②, the bare cell B is placed in the outer areas ①③ and ④, and the active mass ratio k in the entire cell is 0.35.

[0128] Comparative Example 1

[0129] The preparation process of the lithium-ion battery is generally similar to that of Example 1, except that all the bare cells are bare cells A.

[0130] Comparative Example 2

[0131] The preparation process of the lithium-ion battery is generally similar to that of Example 1, except that all the bare cells are bare cells B.

[0132] Comparative Example 3

[0133] The preparation process of the lithium-ion battery is generally referred to Example 1, except that all the bare cells are bare cells B, and the positive electrode active material of the bare cells B is a physical mixture of single crystal NCM523 + polycrystalline NCM712, and the mixing mass ratio is 5:5.

[0134] The lithium ion batteries prepared in the examples and comparative examples were subjected to performance tests, and the measurement methods of each performance test were as follows:

[0135] Cyclic performance test (capacity retention rate 1000 cycles): Under the condition of temperature of 25±2℃, an initial pressure of 2000±300N is applied to the battery, the battery is charged to 4.35V with a step-by-step charging strategy, and then the battery is discharged to 2.8V with a current of 1C, and the capacity retention rate of the battery after 1000 cycles is recorded. The test results are shown in Table 1.

[0136] Gas production performance test (70℃, 4.35V, 40 days of storage): In the battery manufacturing process, the battery cell is retained before the sealing nail is welded to make a gas-producing battery cell. The production and testing process of the gas-producing battery cell is as follows: the gas-producing nail is laser welded at the liquid injection port, and the other end of the gas-producing nail is connected to a plastic hose filled with silicone oil, and the other end of the plastic hose is connected to a gas pressure gauge. Gas production test conditions: for an initial pressure of 2000±300N on the battery, the battery is fully charged to 4.35V, tested in a 70℃ high-temperature furnace (stored for 40 days), and the changes in the gas pressure gauge are recorded. The test results are shown in Table 1.

[0137] Battery capacity test: At a temperature of 25±2℃, discharge the battery to 2.8V at a current of 1 / 3C, then charge the battery to 4.35V at a current of 1 / 3C, charge the battery at a constant voltage until the current drops to 0.05C to fully charge the battery, and finally discharge the battery to 2.8V at a current of 1 / 3C. The value obtained is the initial battery capacity C0 of the battery.

[0138] Battery energy density test: During the battery capacity test, the battery goes from a fully charged state (100% SOC) to a fully discharged state (0% SOC), and the discharge voltage-capacity curve is integrated to obtain the total discharge energy of the battery. Battery energy density = total discharge energy of the battery / total weight of the battery.

[0139] Battery shell thickness group margin: For hard shell cells, it is the thickness of the bare cell after winding / the maximum thickness left for the cell inside the shell, which is reserved to ensure assembly and subsequent expansion.

[0140] XRD: X-ray powder crystal diffraction technology (X-ray Diffraction, XRD) is one of the most commonly used characterization methods for analyzing material structure. The periodic repetitive structure of the crystal enables it to produce a diffraction effect on X-rays. The position of the X-ray diffraction line is related to the unit cell parameters (unit cell shape and size), that is, it is determined by the distance between each crystal plane; the relative intensity of the diffraction line is determined by the type, number and arrangement of atoms in the unit cell. The diffraction of X-rays on a specific crystal material reflects a specific crystal structure diffraction pattern, so that the physical structure of the material can be analyzed through the diffraction pattern. The powder crystal diffraction method has serious overlap in diffraction peaks, which makes it difficult to separate and obtain accurate diffraction intensity values. The structural crystal information is lost, and it is difficult to obtain accurate crystal structure data. Hugo M. Rietveld proposed a Rietveld full spectrum fitting method for correcting the crystal structure by full spectrum fitting of polycrystalline diffraction data. Based on a given initial crystal structure model and parameters, a suitable peak shape function is used to calculate the diffraction spectrum, and the crystal structure parameters and peak shape parameters are continuously adjusted by the least square method to make the calculated spectrum and the experimental spectrum gradually match, thereby obtaining the corrected structural parameters. The data refinement software used in this application is General Structure Analytic System (GSAS) software for Rietveld structure refinement (Toby BHEXPGUI, a graphical user interface for GSAS [J]. Journal of Applied Crystallography, 2001, 34, 210-213).

[0141] Electrochemical in-situ XRD is an important method for testing the structural evolution of materials during the charge and discharge process. Testing in-situ XRD usually requires the use of a high-energy synchrotron radiation source. Synchrotron radiation is a very strong electromagnetic radiation emitted along the tangent direction of the track curve when high-energy charged particles with speeds close to the speed of light move in a magnetic field. Synchrotron radiation sources have the characteristics of wide band, high collimation, high polarization, high purity and high brightness. Synchrotron radiation in-situ XRD electrolytic cell design Fig. 9 As shown, Kapton film is used as the sealing window, and the test mode is the transmission mode.

[0142] The experimental synchrotron X-ray diffraction in this application was carried out at the beam 11-ID-D of the Advanced Light Source at Argonne National Laboratory in the United States. The X-ray diffraction wavelength is The test range is 10-80°, and a flat-panel detector is used to collect data, with a sampling interval of approximately 10 minutes.

[0143] During the charging process of the battery (from fully discharged state 0% SOC to fully charged state 100% SOC), the positive electrode continuously delithiates. For ternary materials, the diffraction peaks of the material can be attributed to the ɑ-NaFeO2 hexagonal layered structure with R-3m space group. During the lithium ion extraction process, the change in the interplanar spacing between the (003) peak and the (110) peak in the XRD spectrum represents the change in the unit cell parameters c and a. The in-situ battery was charged and discharged for the first cycle to obtain the XRD patterns of the positive electrode at different delithiation states (SOC). The XRD patterns of different delithiation states were Rietveld refined using GSAS software to obtain the changes in the unit cell parameters a and c of different delithiation states. The unit cell volume V=a was calculated using the unit cell parameters. 2 *c*sin120°, so that the unit cell volume change of the positive electrode at different delithiation states (SOC) can be obtained (see Figure 8 ): Based on the XRD pattern of the initial fully lithium-embedded positive electrode (corresponding to 0% SOC of the whole battery), the Rietveld fitting method is used to obtain the unit cell parameters c0 and a0, and the initial unit cell volume V0 is calculated. As charging proceeds, the lithium ions in the positive electrode are continuously released (corresponding to the increase in the SOC of the whole battery), and the XRD patterns of the positive electrode in different delithiation states (SOC) are obtained. The Rietveld fitting method is used to obtain the unit cell parameters c and a in different delithiation states of the positive electrode, and the unit cell volume V is calculated. Thus, the unit cell volume change of the positive electrode in different delithiation states (SOC) can be obtained = (V-V0) / V0. When the value of the unit cell volume V corresponds to the state of 100% SOC of the whole battery, the above formula is used to calculate the 100% SOC charging unit cell volume shrinkage rate. SOC: State of Charge, refers to the percentage of remaining battery power, 100% is a fully charged state, and 0% is a fully discharged state.

[0144] Table 1

[0145]

[0146] According to the above Table 1, it can be seen that the embodiments of the present application can obtain better comprehensive performance than the comparative examples, and can avoid the diving trend or excessive gas production of lithium-ion batteries. Specifically, it can be seen from Example 1 relative to Comparative Examples 1 and 2, and from Example 3 relative to Comparative Example 3 that when different positive bare cells are used in the battery cell, the lithium-ion battery can obtain better comprehensive performance, and can avoid the diving trend or excessive gas production of the lithium-ion battery.

[0147] In addition, although as mentioned above, the embodiments of the present application can obtain better comprehensive performance than the comparative examples, and can avoid the diving trend or excessive gas production of lithium-ion batteries, it can be found from Example 1 compared with Example 8 that when the bare battery cell B including the polycrystalline high-nickel material is placed outside the battery cell, the lithium-ion battery can obtain better cycle performance. When the cycle reaches 1000 cycles, the capacity retention rate of Example 1 is significantly improved compared with Example 8.

[0148] Through other embodiments compared with embodiments 9 and 10, it can be found that when the proportion of high-nickel active materials is too large, the gas production performance of the lithium-ion battery may deteriorate. When the proportion of high-nickel active materials is too small, the cycle expansion may not be significantly improved. In the later stage of the battery cycle, the expansion force is large, lithium is deposited in the middle section of the bare cell, and the cycle water drop may occur.

[0149] It can be found from Example 7 that a polycrystalline ternary positive electrode material with a lower nickel content can be further introduced into the bare battery cell B to improve the overall performance of the lithium-ion battery. Although the introduction of this material may lead to a relative deterioration in the gas production performance, it is combined with the ternary positive electrode material with a higher nickel content in the bare battery cell B to improve the overall performance of the lithium-ion secondary battery.

[0150] It can be found from Examples 3 and 4 that a single crystal or quasi-single crystal ternary positive electrode material with a lower nickel content can be further introduced into the bare battery cell B, which can improve the comprehensive performance of the lithium-ion battery. While ensuring that the cycle expansion is improved, the gas production performance will also be better, and the lithium-ion battery has better comprehensive performance when the k value is in an appropriate range.

[0151] In summary, the present invention effectively overcomes various shortcomings of the prior art and has high industrial utilization value.

[0152] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A lithium ion secondary battery, characterized in that: It includes a bare cell accommodating cavity, in which a bare cell group is arranged, the bare cell accommodating cavity includes one or more bare cells A, and one or more bare cells B, the bare cell A includes a first positive electrode plate, the first positive electrode plate includes a first positive electrode active substance, the first positive electrode active substance is selected from a single crystal or quasi-single crystal low-nickel ternary positive electrode material A1, the bare cell B includes a second positive electrode plate, the second positive electrode plate includes a second positive electrode active substance and / or a third positive electrode active substance, the second positive electrode active substance is selected from a polycrystalline high-nickel ternary positive electrode material B1, and the third positive electrode active substance is selected from a polycrystalline low-nickel ternary positive electrode material B2.

2. The lithium ion secondary battery according to claim 1, characterized in that: The molecular formula of the single crystal or quasi-single crystal low-nickel ternary positive electrode material A1 is LiNi x1 Co y1 Mn 1-x1-y1 O2, wherein 0<x1≤0.65, 0<y1<0.35, 0<1-x1-y1<0.

35.

3. The lithium ion secondary battery according to claim 1, characterized in that: The molecular formula of the single crystal or quasi-single crystal low-nickel ternary positive electrode material A1 is LiNi x1 Co y1 Mn 1-x1-y1 O2, wherein 0<x1≤0.55, 0<y1<0.45, 0<1-x1-y1<0.

45.

4. The lithium ion secondary battery according to any one of claims 1 to 3, characterized in that The molecular formula of the polycrystalline high nickel ternary positive electrode material B1 is LiNi x2 Co y2 Mn 1-x2-y2 O2, where 0.7≤x2<1, 0<y2<0.3, 0<1-x2-y2<0.

3.

5. The lithium ion secondary battery according to any one of claims 1 to 3, characterized in that The molecular formula of the polycrystalline high nickel ternary positive electrode material B1 is LiNi x2 Co y2 Mn 1-x2-y2 O2, wherein 0.7≤x2≤0.8, 0.2<y2<0.3, 0.2<1-x2-y2<0.

3.

6. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that The molecular formula of the polycrystalline low-nickel ternary positive electrode material B2 is LiNi x3 Co y3 Mn 1-x3-y3 O2, where 0 <x3≤0.65,0<y3<0.35,0<1-x3-y3<0.35。 7. The lithium ion secondary battery according to any one of claims 1 to 5, characterized in that The molecular formula of the polycrystalline low-nickel ternary positive electrode material B2 is LiNi x3 Co y3 Mn 1-x3-y3 O2, wherein 0<x3≤0.55, 0<y3<0.45, 0<1-x3-y3<0.

45.

8. The lithium ion secondary battery according to any one of claims 1 to 7, characterized in that The 100% SOC charging unit cell volume shrinkage rate of the single crystal or quasi-single crystal low-nickel ternary positive electrode material A1 is ≤3%; And / or, the 100% SOC charging unit cell volume shrinkage rate of the polycrystalline high-nickel ternary positive electrode material B1 is ≥4%; And / or, the 100% SOC charging unit cell volume shrinkage rate of the polycrystalline low-nickel ternary positive electrode material B2 is ≤3%.

9. The lithium ion secondary battery according to any one of claims 1 to 8, characterized in that Compared with the bare battery cell A, the bare battery cell B is distributed closer to the outside of the bare battery cell group.

10. The lithium ion secondary battery according to any one of claims 1 to 9, characterized in that Compared with the bare battery cell B, the bare battery cell A is distributed closer to the middle of the bare battery cell group.

11. The lithium ion secondary battery according to any one of claims 1 to 10, characterized in that: The second positive electrode plate further comprises a fourth positive electrode active material, the fourth positive electrode active material is selected from a single crystal or quasi-single crystal low-nickel ternary positive electrode material A2, the molecular formula of the single crystal or quasi-single crystal low-nickel ternary positive electrode material A2 is LiNi x4 Co y4 Mn 1-x4-y4 O2, where 0 <x4≤0.65,0<y4<0.35,0<1-x4-y4<0.35。 12. The lithium ion secondary battery according to any one of claims 1 to 10, characterized in that: The second positive electrode plate further comprises a fourth positive electrode active material, the fourth positive electrode active material is selected from a single crystal or quasi-single crystal low-nickel ternary positive electrode material A2, the molecular formula of the single crystal or quasi-single crystal low-nickel ternary positive electrode material A2 is LiNi x4 Co y4 Mn 1-x4-y4 O2, wherein 0<x4≤0.55, 0<y4<0.45, 0<1-x4-y4<0.

45.

13. The lithium ion secondary battery according to claim 11 or 12, characterized in that: The 100% SOC charging unit cell volume shrinkage rate of the single crystal or quasi-single crystal low-nickel ternary positive electrode material A2 is ≤3%.

14. The lithium ion secondary battery according to any one of claims 1 to 13, characterized in that: In the lithium ion secondary battery, a mass ratio k of the total mass of the single crystal positive electrode active material to the total mass of the polycrystalline positive electrode active material is 0.5-9.

15. The lithium ion secondary battery according to any one of claims 1 to 14, characterized in that: The coating amount of the negative electrode in the bare battery cell A is ≤0.150g / 1540.25mm^2.

16. A battery module, characterized in that: A lithium ion secondary battery comprising the lithium ion secondary battery according to any one of claims 1 to 15.

17. A battery pack, characterized in that: A battery module comprising the battery module described in claim 16.

18. An electrical device, characterized in that: The battery comprises at least one selected from the lithium ion secondary battery according to any one of claims 1 to 15, the battery module according to claim 16, or the battery pack according to claim 17.

Citation Information

Patent Citations

  • Positive electrode sheet capable of discharging at high rate, and lithium ion battery comprising positive electrode sheet

    CN112151793A

  • Positive electrode sheet capable of discharging at high rate, and lithium ion battery comprising positive electrode sheet

    CN112151794A

  • Multi-layer cathode with nickel gradient

    CN112701258A

  • Lithium ion secondary battery and positive pole piece thereof

    CN112751032A

Cited By

  • Selection method and production method of nickel-cobalt-manganese-based active material for positive electrode

    KR1020240151646A

  • Selection method and production method of nickel-cobalt-manganese-based active material for positive electrode

    KR102974195B1

  • Determining methods for performance of cycle life of alkali metal ion batteries and operating methods thereof

    TWI927824B